HUKUM CAGAR BUDAYA DAN KORESPONDENSINYA DENGAN PERLINDUNGAN BANGUNAN PENINGGALAN KOLONIAL BELANDA DI INDONESIA - Noor Tri Hastuti (Perspektif, 2002)
Normatively, the preventive regulation of nature and archaeological preservation, including ancient Dutch Colonial buildings has been set, i.e. UU of environment and of lay out planning. It is intended to optimally avoid the destruction of Indonesian culture and “profit oriented only” building constructions. It is also expected to increase the responsibility of the government officers as the person in charge in the preservation scheme of historical valuables.